Pengaruh Pengungkapan Informasi Lingkungan, Kinerja Lingkungan, dan Komite Audit Terhadap Kinerja Keuangan - Muzaki, Muhammad; Husnaini, Wahidatul (Jurnal Akuntansi & Keuangan Unja, 2025)
This study aims to empirically examine the effect of environmental information disclosure, environmental performance, and audit committees on the financial performance of mining companies listed on the Indonesia Stock Exchange (IDX) during the period 2019-2023. This study uses a quantitative approach, with a total of 114 observations. Hypothesis testing using multiple linear regression, descriptive statistical analysis, and pairwise correlation tests using Stata 17 software. The results of the study indicate that environmental information disclosure and audit committees do not influence financial performance, while environmental performance has a significant positive influence on financial performance. Firm size does not influence financial performance, while leverage has a significant negative influence on financial performance. The findings of this study provide important implications for corporate governance and sustainability practices in the mining sector. The results also imply that audit committees may not optimally perform their monitoring role in enhancing financial performance, highlighting the need to strengthen their effectiveness.